Swami Vivekananda's vedāntic cosmopolitanism - Maharaj, Ayon (Oxford University Press, 2022)
"Swami Vivekananda, the nineteenth-century Hindu monk who introduced Vedānta to the West, is undoubtedly one of modern India's most influential philosophers. Unfortunately, his philosophy has too often been interpreted through reductive hermeneutic lenses. Typically, scholars have viewed him either as a modern-day exponent of Śaṅkara's Advaita Vedānta or as a "Neo-Vedāntin" influenced more by Western ideas than indigenous Indian traditions. In Swami Vivekananda's Vedāntic Cosmopolitanism, Swami Medhananda rejects both of these prevailing approaches to offer a new interpretation of Vivekananda's philosophy, highlighting its originality, contemporary relevance, and cross-cultural significance. Vivekananda, the book argues, is best understood as a cosmopolitan Vedāntin who developed novel philosophical positions through creative dialectical engagement with both Indian and Western thinkers. Inspired by his guru Sri Ramakrishna, Vivekananda reconceived Advaita Vedānta as a nonsectarian, life-affirming philosophy that provides an ontological basis for religious cosmopolitanism and a spiritual ethics of social service. He defended the scientific credentials of religion while criticizing the climate of scientism beginning to develop in the late nineteenth century. He was also one of the first philosophers to defend the evidential value of supersensuous perception on the basis of general epistemic principles. Finally, he adopted innovative cosmopolitan approaches to long-standing philosophical problems. Bringing him into dialogue with a galaxy of contemporary philosophers, Medhananda demonstrates the sophistication and enduring value of Vivekananda's views on the limits of reason, the dynamics of religious faith, and the hard problem of consciousness"--